Short-term effects of ambient air pollution on pediatric outpatient visits for respiratory diseases in Yichang city, China. (August 2017) - Liu, Yuewei; Xie, Shuguang; Yu, Qing; Huo, Xixiang; Ming, Xiaoyan; Wang, Jing; Zhou, Yun; Peng, Zhe; Zhang, Hai; Cui, Xiuqing; Xiang, Hua; Huang, Xiji; et al.
Abstract: Previous studies have suggested that short-term exposure to ambient air pollution was associated with pediatric hospital admissions and emergency room visits for certain respiratory diseases; however, there is limited evidence on the association between short-term air pollution exposure and pediatric outpatient visits. Our aim was to quantitatively assess the short-term effects of ambient air pollution on pediatric outpatient visits for respiratory diseases. We conducted a time-series study in Yichang city, China between Jan 1, 2014 and Dec 31, 2015. Daily counts of pediatric respiratory outpatient visits were collected from 3 large hospitals, and then linked with air pollution data from 5 air quality monitoring stations by date. We used generalized additive Poisson models to conduct linear and nonlinear exposure-response analyses between air pollutant exposures and pediatric respiratory outpatient visits, adjusting for seasonality, day of week, public holiday, temperature, and relative humidity. Each interquartile range (IQR) increase in PM2.5 (lag 0), PM10 (lag 0), NO2 (lag 0), CO (lag 0), and O3 (lag 4) concentrations was significantly associated with a 1.91% (95% CI: 0.60%, 3.23%), 2.46% (1.09%, 3.85%), 1.88% (0.49%, 3.29%), 2.00% (0.43%, 3.59%), and 1.91% (0.45%, 3.39%) increase of pediatric respiratory outpatient visits, respectively. Similarly, the nonlinear exposure-response analyses showed monotonic increases of pediatric respiratory outpatient visits by increasing air pollutant exposures, though the associations for NO2 and CO attenuated at higher concentrations. These associations were unlikely modified by season. We did not observe significant association for SO2 exposure. Our results suggest that short-term exposures to PM2.5, PM10, NO2, CO, and O3 may account for increased risk of pediatric outpatient visits for respiratory diseases, and emphasize the needs for reduction of air pollutant exposures for children. Graphical abstract: Highlights: PM2.5, PM10, NO2, CO exposures (no lag) may account for increased pediatric respiratory outpatient visits. O3 exposure (lag 4 days) was associated with increased pediatric respiratory outpatient visits. The exposure-response associations were relatively robust. Season was unlikely to modify these associations. This study emphasizes needs to reduce air pollutant exposures for children. Abstract : This study provided further evidence that short-term exposures to air pollution have adverse effects on children's health, and that reduction of air pollutant exposure is needed to protect children.